Quantifying ecosystem responses to environmental and human pressures in the marine ecosystem off the west coast of Vancouver Island. (December 2021) - Boldt, Jennifer L.; Hazen, Elliott L.; Hunsicker, Mary E.; Fu, Caihong; Perry, R. Ian; Shan, Xiujuan
Highlights: We examined pressure-response indicator relationships using a multi-model approach. Nonlinear and linear pressure-response relationships were rare (6–12%). Ecological responses were more commonly associated with environmental than human pressures. Multivariate analyses helped validate the results from single pressure-response models. Dimension reducing analyses on multiple indicators may result in information loss. Abstract: One necessity of ecosystem based management is an understanding of the shape and functional forms of ecosystem responses to environmental and human pressures. Both nonlinear and linear relationships may provide leading indicators of ecosystem change and inform reference points for ecosystem approaches to management. The objectives of this study were to 1) determine functional forms of pressure-response relationships, 2) identify non-linear relationships, and 3) quantify potentially relevant management thresholds for the west coast of Vancouver Island marine ecosystem in British Columbia, Canada. To do this, a multi-model approach was applied to mechanistically linked indicators of pressures and responses. Both single pressure-response and multivariate relationships were examined. Results indicate that 1) nonlinear and linear relationships were not prevalent with the percentage of occurrence (6–12%) similar to other regions, 2) ecological responses (both linear and nonlinear) were more commonly associated with environmental pressures than human pressures, 3) gradient forest analysis generally produced similar results as single pressure-response models and identified additional nonlinearities, 4) dynamic factor analyses (DFA) reduced the numerous pressure and response indicator to a few trends, however, the process may have resulted in a loss of information, and 5) possibly due to this loss of information, gradient forest and single pressure-response analyses on DFA trends produced different results. Quantifying how pressures affect ecosystem components can provide advanced knowledge about changes in ecosystem productivity, structure, and function which can inform science advice and management strategies. Mechanistically linked pressure-response relationships should be explored further with multi-model ensembles to better inform ecosystem-based and climate-ready approaches to marine management.